2020
DOI: 10.2478/hukin-2019-0136
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Parasympathetic Reactivation Following Small‐Sided Games, Repeated Sprints and Circuit Training in Elite Handball Players

Abstract: To compare acute parasympathetic reactivation following usual training exercises, the acute post-exercise heart rate (HR) and heart rate variability (HRV) were analysed. Fourteen elite male handball players completed three separate sessions of 16-min small-sided games (SSGs), repeated sprints (RSs) consisting of two sets of six repetitions of a 25-m sprint with a 180° change of direction (12.5 m + 12.5 m) every 25 s and 40 min of handball-specific circuit training (CT, one brief action every 40 s). The HR was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…However, in another study [17], the same linearity of the results was not observed. the comparison between SSGs and sprint training presented discrepant results concerning the method promoting higher levels of maximum heart rate [5,33]. the rated perceived exertion also presented divergences in results, with both a linear increase associated with a rise in the pitch area [17] and non-linearity of results observed [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in another study [17], the same linearity of the results was not observed. the comparison between SSGs and sprint training presented discrepant results concerning the method promoting higher levels of maximum heart rate [5,33]. the rated perceived exertion also presented divergences in results, with both a linear increase associated with a rise in the pitch area [17] and non-linearity of results observed [16].…”
Section: Discussionmentioning
confidence: 99%
“…Acutely, SSG training (composed of 2 sets of 8' 30'' stimuli/30'' passive recovery, with the entire game 3vs3), when compared with sprint training, presented lower results for the percentage of time of heart rate above 90% of maximum heart rate [33]. In turn, Ravier and Marcel-Millet [5] compared the acute effects of SSG, sprint training, and handball-specific circuit training; SSG was associated with higher levels of mean heart rate and maxi-mum heart rate as compared with the other methods.…”
Section: Chronic Effects Of Ssgmentioning
confidence: 96%
See 1 more Smart Citation
“…Figure 2 shows that many HRV indices remained decreased for at least 60 min after the end of handball training (e.g., moderate ES for lnRMSSD and large ES for RR with PAS6; moderate ES for lnHF with PAS323). After various endurance (Kaikkonen et al, 2010;Michael et al, 2017b;Seiler et al, 2007) and team sport (Flatt and Howells, 2019;Ravier and Marcel-Millet, 2020) exercises, previous studies reported that intensity was the exercise characteristic having the greatest impact on delaying post-exercise HRV recovery. The post-exercise cardiac parasympathetic disruption observed was up to 50 min after exercise performed until exhaustion in physically active males (Almeida et al, 2016), and 60 min after a Crossfit® workout in healthy adults (Kliszczewicz et al, 2016).…”
Section: Table 4 Qualitative Comparison Between Post-training and Pos...mentioning
confidence: 99%
“…The magnitude and duration of parasympathetic disruption during recovery appeared to be related to exercise variables (i.e., intensity, duration and modality) and individual characteristics (i.e., physical fitness, recovery potential, mood state) (Kaikkonen et al, 2010;Michael et al, 2017;Nakamura et al, 2016;Seiler et al, 2007). The time course of parasympathetic recovery has been widely analyzed to assess the responsiveness of the autonomic nervous system and to reflect indirectly the overall recovery status of players (Ravier & Marcel-Millet, 2020;Stanley et al, 2013). During intense training, the importance of maintaining a high level of parasympathetic activity to trigger positive adaptations was reported (Nakamura et al, 2016(Nakamura et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%